Trends and Opportunities in ESG Research within Sustainability Accounting: A Bibliometric Analysis - Praningtyas, Elisabeth Ria Viana; Adi, Alif Mundi (The Indonesian Journal of Accounting Research, 2025)
Awareness of environmental issues has been increasing over the past decade. At the international level, this heightened awareness has prompted many countries to focus on sustainability. Along with the growing awareness of sustainability, research on ESG in relation to sustainability accounting has also increased significantly. This study aims to map ESG research in the context of sustainability accounting through bibliometric analysis. From this mapping, we can analyze publication trends, popular research topics, contributions from institutions and researchers, and the interconnections between ESG topics and sustainability accounting. This bibliometric analysis not only helps to understand the development of ESG literature but also provides a clear picture of underexplored or underdeveloped areas that require further research. The study analyzes 151  articles and conference proceedings indexed in Scopus that relate to ESG in the context of sustainability accounting. The findings indicate that research on ESG themes in the context of sustainability accounting remains relevant and promising. Researchers can explore topics such as greenhouse gas emissions and the Global Reporting Initiative, which are underdeveloped yet strongly connected to ESG themes in sustainability accounting. As a result, the research conducted provides novelty in the field.